1D/2D nanoconfinement FexOy and nitrogen-doped carbon matrix for catalytic self-cleaning membranes removal for pollutants. Issue 5 (October 2021) - Ye, Jian; Dai, Jiangdong; Yang, Dayi; Li, Chunxiang; Yan, Yongsheng
Abstract: Catalytic performance and practical applications of catalysts are two key problems in wastewater treatment through activating peroxymonosulfate (PMS). Herein, 1D/2D nitrogen-doped carbon matrix with confined Fex Oy was firstly developed through in-situ pyrolysis of dual metal-organic frameworks (named as ZIF@MILs-20). Subsequently, graphene oxide (GO) supported composite membranes were constructed through intercalating ZIF@MILs-20 into adjacent GO. Studies have proven that enriched oxygen vacancies, confined Fex Oy and 1D/2D hierarchically porous structures of ZIF@MILs-20 were favorable for the elimination of norfloxacin (NX) through a synergistic "trap-and-zap" strategy for PMS activation. As expected, 99.4% NX over ZIF@MILs-20/PMS system was degraded after 40 min. Further, abundant oxygen-containing groups on GO composite membranes strongly improved the wettability of catalysts that shorten the reaction distance between reactive oxidative species (ROS) and active sites. Thus ZIF@MILs-20/GO membrane provided instantaneous elimination of norfloxacin for up to 10 h under flow-through filtration. Notably, ZIF@MILs-20/GO membrane realized the membrane filtration-catalytic oxidation of organics, powerfully overcoming the membrane fouling with a stable flux of 156.3 L·m −2 ·h −1 ·bar −1 . Besides, singlet oxygen ( 1 O2 ) was proven that dominantly contributed to the NX degradation. In short, the construction of catalytic membranes provides a new idea for wastewater treatment. Graphical Abstract: ga1 Highlights: 1D/2D nanoconfinement Fex Oy and nitrogen-doped carbon matrix was developed. GO composite membranes were constructed through intercalating ZIF@MILs-20 into adjacent GO. 99.4% NX was degraded through a synergistic "trap-and -zap" strategy. ZIF@MILs-20/GO membrane provided instantaneous elimination of norfloxacin for up to 10 h. singlet oxygen dominated the NX degradation.